Comparison of nanofluid heat transfer properties with theory using generalized property relations for EG-water mixture - Vandrangi, S.K. (EDP Sciences, 2017)
A numerical analysis for the determination for turbulent characteristics of fluid flow and heat transfer have been developed by employing the eddy diffusivity equation of Van Driest. The properties of Silicon dioxide (SiO2) nanofluid with spherical particles in base liquid ethylene glycol (EG) -water (W) mixture of 60:40 ratio is employed for a wide range of concentrations and bulk temperature. A good agreement of the numerical results with the experimental data for properties and heat transfer is observed. A comparison of Copper oxide (CuO), Aluminum dioxide (Al2O3) and Silicon dioxide (SiO2) nanofluids revealed that SiO2 attain higher temperature gradients in comparison to CuO nanofluid at the same concentration and temperature. © The authors, published by EDP Sciences, 2017.